Weed Management Potentials of Identified Invasive Weed Species - Carcusia, Annabella; Rosit, James Francienne; Pascual, Pet Roey (JPAIR Multidisciplinary Research, 2015)
Synthetic herbicide, the most popular weed control, causes environmental hazards. The use of allelopathy in controlling weeds is a possible alternative for sustainable weed management. The study was conducted to determine the allelopathic potentials of identified invasive weed species in terms of percent and rate of germination, plant height, length of leaves and roots and percent mortality of grasses, sedges, and broadleaves. The treatments were: T0-Pre/Post-emergence Herbicide, T1Tap Water, T2-Mimosa pudica extract,T3-Lantana camara extract,T4-Chromolaena odorata extract. These were compared according to their effects on Cenchrus spinifex, Conyza canadensis, Impatiens wallerana and Cyperus rotundus. Data were analyzed using Analysis of Variance (ANOVA) for Completely Randomized Design. A further test was done using Duncans Multiple Range Test (DMRT). For germination, Lantana camara is effective in reducing the percent germination and prolonging germination rate of most common weed species. On the other hand, Chromolaena odorata is effective in reducing the percent germination and prolonging the germination rate of Impatiens wallerana, while Mimosa pudica was effective against Cenchrus spinifex and Cyperus rotundus. For growth and development, Mimosa pudica was found to be the most effective in all common weed species, except for Cyperus rotundus where Chromolaena odorata was most effective on reducing the length of leaves and roots, and above ground fresh weight. Furthermore, Chromolaena odorata was found effective against both Cyperus rotundus and Conyza canadensis while Mimosa pudica was effective against Cenchrus spinifex in terms of percent mortality. Thus, such potential of invasive weed species for weed management should be utilized.